2019
DOI: 10.1536/ihj.18-076
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Electrocardiogram Features Across Sleep Stages in Healthy Controls and in Patients with Sleep Apnea Hypopnea Syndrome

Abstract: Sleep apnea hypopnea syndrome (SAHS) is an independent risk factor for various cardiovascular diseases. Electrocardiogram (ECG) features such as the RR, PR, QT, QTc, Tpe intervals and the Tpe/QT, Tpe/QTc ratios are used to predict and study cardiovascular diseases. It is not clear whether regular patterns of PR and Tperelated features across sleep stages exist in SAHSs or healthy controls nor whether sleep stages affect the shortand long-range influences of respiratory events on ECG indices. We enrolled 36 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Both original studies were approved by the relevant ethics boards (California Clinical Trials, Glendale; Spaulding Clinical Services, Milwaukee; Parexel International, Baltimore) and all participants gave written informed consent according to the Helsinki declaration. Because of the known effect of sleep on the QT interval duration 14 which might be expected also for the JTp and JT50 intervals 15 , the present study used only day-time portions of the recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Both original studies were approved by the relevant ethics boards (California Clinical Trials, Glendale; Spaulding Clinical Services, Milwaukee; Parexel International, Baltimore) and all participants gave written informed consent according to the Helsinki declaration. Because of the known effect of sleep on the QT interval duration 14 which might be expected also for the JTp and JT50 intervals 15 , the present study used only day-time portions of the recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the evidence regarding altered autonomic system activity in OSA patients, previous results regarding QTc interval variations in OSA patients are conflicting. Zeng et al reported a decrease in QTc as sleep gets deeper and an increase in QTc during REM sleep—the highest QTc intervals in REM sleep [ 9 ]. Lanfranchi et al showed insignificant changes in QTc intervals during wake, N2, and N3 sleep and a significant increase in REM sleep [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the variations of QTc intervals in different sleep stages are also conflicting. While studies show different trends or insignificant changes in QTc interval toward deeper sleep stages in non-rapid eye movement (non-REM) stages, the longest QTc intervals are reported to occur in REM sleep [ 9 , 15 , 16 ]. However, in these studies, variations of QTc intervals were not investigated separately in different sleep stages and during wake [ 9 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ECG is a widely used method for monitoring and assessing a patient’s physical and mental health condition. This is particularly relevant for sleep apnoea syndrome (SAS), where respiratory events are known to affect ECG features [1]. SAS is a prevalent disorder characterized by pauses in breathing or periods of shallow breathing during sleep, potentially resulting in cardiovascular morbidity and increased daytime sleepiness, with associated risk for car accidents [2,3].…”
Section: Introductionmentioning
confidence: 99%